Back Cover: Magnetic Topological Semimetal Phase with Electronic Correlation Enhancement in SmSbTe (Adv. Quantum Technol. 10/2021). Issue 10 (8th October 2021) - Pandey, Krishna; Mondal, Debashis; Villanova, John William; Roll, Joseph; Basnet, Rabindra; Wegner, Aaron; Acharya, Gokul; Nabi, Md Rafique Un; Ghosh, Barun; Fujii, Jun; Wang, Jian; Da, Bo; et al.
Abstract : Topological materials are a promising platform for a wide range of next‐generation technologies. In article number 2100063, Antonio Politano, Salvador Barraza‐Lopez, Jin Hu and co‐workers report a new topological material, SmSbTe, displaying a coexistence of magnetism, enhanced electronic correlations, and Dirac fermions, as illustrated in the cover image. This discovery suggests that SmSbTe represents an ideal platform for exotic quantum phenomena arising from the interplay between degrees of freedom. The manipulation of these phenomena would further pave a path for quantum material‐based functional devices.